2010
DOI: 10.3109/00016480903071377
|View full text |Cite
|
Sign up to set email alerts
|

Human papillomavirus (HPV)-positive tonsillar carcinomas are frequent and have a favourable prognosis in males in Norway

Abstract: HPV was found in 71/137 (52%) of the tumours; HPV-16 was the most frequent subtype (87%). HPV positivity did not correlate with gender, stage, T- and N categories, Ki-67 expression or p53 positivity. The HPV-positive group had a significantly better survival (p < 0.01) compared with the HPV-negative group in males. In a multivariate analysis HPV status gave prognostic information in addition to the earlier established factors, i.e. age, gender and stage (p < 0.05).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
17
0
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(21 citation statements)
references
References 19 publications
3
17
0
1
Order By: Relevance
“…It is possible that DNA integrity is lower in older samples. Previous studies of OSCC samples from 1960s and 1970s showed that adequate HPV DNA can be extracted in 69% to 77% of cases [12,13]. We have recently reported our experience of testing mucoepidermoid carcinomas for CRCT1-MAML2 translocation by fluorescence ISH [28].…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…It is possible that DNA integrity is lower in older samples. Previous studies of OSCC samples from 1960s and 1970s showed that adequate HPV DNA can be extracted in 69% to 77% of cases [12,13]. We have recently reported our experience of testing mucoepidermoid carcinomas for CRCT1-MAML2 translocation by fluorescence ISH [28].…”
Section: Discussionmentioning
confidence: 94%
“…Few studies have used actual tumor tissue to characterize the HPV incidence in OSCC over several decades. In Sweden and Norway, the increase in HPV-positive cases of OSCC was demonstrated using samples dating back to the 1960 to 1970s [12,13]. In the United States, the "oldest" set of OSCC tested for HPV dates back to 1975 [14].…”
Section: Introductionmentioning
confidence: 97%
“…22,23 These studies did not include healthy controls, but the data suggest an etiological role for HPV. Apparently these viruses may be responsible for transformation of epithelia in the cervix, and in the alimentary tract beyond the oral cavity, but rarely in the oral cavity.…”
Section: Discussionmentioning
confidence: 95%
“…13,16,17 The two PCR primer sets were designed to detect high risk, dysplasia associated HPV subtypes, including HPV 16 and 18, and have been used extensively for this purpose. 6,10,22 The products were analyzed in 2% agarose gel stained with ethidium bromide. The blank samples were consistently negative in PCR.…”
Section: Pcrmentioning
confidence: 99%
“…Evidence in the contemporary literature suggests that patients with HPV OSCC have an improved 5-year overall survival rate: 75% for patients with HPV+ OSCC versus 45% among patients with HPV-negative tumors [15,16]. The extent to which the improved overall survival of HPV+ OSCC relies on the administered therapy is unclear: while data highlight that HPV+ status is a favorable predictor regardless of treatment strategy [15], other recent findings emphasize the role of radiotherapy in these tumors.…”
Section: Discussionmentioning
confidence: 91%